Mannose and fructose metabolism in red blood cells during cold storage in SAGM. Issue 11 (21st August 2017) - Rolfsson, Óttar; Johannsson, Freyr; Magnusdottir, Manuela; Paglia, Giuseppe; Sigurjonsson, Ólafur E.; Bordbar, Aarash; Palsson, Sirus; Brynjólfsson, Sigurður; Guðmundsson, Sveinn; Palsson, Bernhard
Abstract : BACKGROUND: Alternate sugar metabolism during red blood cell (RBC) storage is not well understood. Here we report fructose and mannose metabolism in RBCs during cold storage in SAGM and the impact that these monosaccharides have on metabolic biomarkers of RBC storage lesion. STUDY DESIGN AND METHODS: RBCs were stored in SAGM containing uniformly labeled 13 C‐fructose or 13 C‐mannose at 9 or 18 mmol/L concentration for 25 days. RBCs and media were sampled at 14 time points during storage and analyzed using ultraperformance liquid chromatography‐mass spectrometry. Blood banking quality assurance measurements were performed. RESULTS: Red blood cells incorporated fructose and mannose during cold storage in the presence of glucose. Mannose was metabolized in preference to glucose via glycolysis. Fructose lowered adenosine triphosphate (ATP) levels and contributed little to ATP maintenance when added to SAGM. Both monosaccharides form the advanced glycation end product glycerate. Mannose activates enzymes in the RBC that take part in glycan synthesis. CONCLUSIONS: Fructose or mannose addition to RBC SAGM concentrates may not offset the shift in metabolism of RBCs that occurs after 10 days of storage. Fructose and mannose metabolism at 4°C in SAGM reflects their metabolism at physiologic temperature. Glycerate excretion is a measure of protein deglycosylation activity in stored RBCs. No cytoprotective effect was observed upon the addition of either fructose or mannose to SAGM.